Assessing the validity of child marriages contracted during the war: A challenge in post-war Sri Lanka - Wijeyesekera, Rose (University of Colombo, 2011)
Background Armed conflicts destroy the peaceful life of any society and instigate social, political, and legal dilemmas. The three decade old armed conflict in Sri Lanka left the country with unforeseen consequences; mostly irreversible. One such disturbing result is the forced marriages of boys and girls below the age of eighteen years and the consequent impregnation of Tamil and Muslim girls living in the Northern, North Eastern and Eastern Provinces of the country. Under-aged marriages take place not only in the North and the East, but in other parts of Sri Lanka as well as anywhere else in the world. However, the circumstances, which prompt child marriages in war situations, are different from those of non-war situations. The life and death situation faced by those who lived in war-torn areas cannot be compared with the child marriages that take place in other areas of the island. On the other hand, the Sri Lankan situation cannot be compared to other post-war countries because almost all other post-war countries in the present world are either Muslim or African, governed by religious/tribal laws, which recognizes child marriages. Hence the article focuses on marriages of Sri Lankan children, who were directly or indirectly forced to choose marriage as a means of averting conscription by armed terrorist groups. There are many reasons for under-aged marriages in the North and East; while the loss of parents due to the war or to the tsunami, poverty and lack of means to overcome poverty are common causes, the major cause for child marriages in these areas is to avoid being abducted and/or forcefully recruited to the terrorist groups which operated in the area. Hence these marriages are corollary of direct or indirect force. There is convincing evidence that Tamil and Muslim children were forcefully abducted and conscripted E\WKHVHXQODZIXOHOHPHQWVGXULQJWKHZDU :KHQWKHVFDOHVRIWKHµEHVW LQWHUHVW RI WKH FKLOG¶ KXQJ RQ WKH EDODQFH EHWZHHQ OLIH DQG GHDWK WKH SDUHQWV RI WKHVH children had no option than to give their children in marriage despite their age and consent; a choice any parent would make, rather than allowing their children to be abducted, used in the war-front and ultimately face death. In this respect girls were more 146 vulnerable than boys, since the insecure atmosphere created the ideal setting for various forms of abuse, many instances of which passed even without being recorded. The General law of Sri Lanka recognizes that marriages of non-Muslims who are below the age of eighteen years are void ab initio. Accordingly, the marriages of Tamil girls, who are governed by the general law in relation to marriage, would be void in the eyes of the existing law. Legality of the marriage of parents largely determines their legal and sociDO VWDWXV DV ZHOO DV WKHLU FKLOGUHQ¶V VWDWXV ,QYDOLG PDUULDJH RI SDUHQWV OHDYHV WKH FKLOGUHQµLOOHJLWLPDWH¶ UHVXOWLQJLQGLVFULPLQDWRU\OHJDODQGVRFLDOFRQVHTXHQFHV As a necessary requirement in post-conflict reconciliation and reconstruction, it becomes necessary to assess the validity of these marriages on the one hand and the violation of human rights of the child victims of early marriage on the other, whilst preserving social stability. These issues are addressed in this article in three broad perspectives: a. Human rights approach± (DUO\PDUULDJHDIIHFWWKHFKLOG¶VULJKWWROLIHLQDEURDGHU VHQVH DQG KDV D SURIRXQG LPSDFW RQ WKH FKLOG¶V SK\VLFDO LQWHOOHFWXDO psychological and emotional wellbeing, hence the best interests of the child. It also iQYROYHV WKH FKLOG¶V ULJKW WR SDUWLFLSDWLRQ LQ GHFLVLRQV DIIHFWLQJ KLV KHU OLIH 7KH article addresses all these human rights aspects. b. International law and family law perspective ±The questions as to the validity of these marriages and the legal status of the children born to them are discussed under the domestic law. Proposals to possible legal reforms are suggested in the light of relevant international standards on the one hand, and Roman-Dutch law proposition on the age of marriage, the concept of putative marriage, applicability of the option of puberty, minor marriages in customary Hindu law and Muslim law and some permissive features that are still recognized in the Kandyan law, on the other. c. Socio-legal perspective ± Since these marriages were effected due to the prevailing socio-political conditions at that time, particularly when the state had no/limited control of the legal and/or administrative functions in these areas, application of the ordinary law of the country would be contrary to the norms of justice. 7KHUHIRUH WKH DSSOLFDELOLW\ RI WKH µGRFWULQH RI QHFHVVLW\¶ DV D ODVW UHVRUW LQ preserving social, legal and political stability by remedying the adverse consequences is examined.